Promoting Savings at Tax Time through a Video-Based Solution-Focused Brief Coaching Intervention - Lance Palmer; Teri Pichot; Irina Kunovskaya (Journal of Financial Therapy, 2016)
Solution-focused brief coaching, based on solution-focused brief therapy, is a well-established practice model and is used widely to help individuals progress toward desired outcomes in a variety of settings. This papers presents the findings of a pilot study that examined the impact of a video-based solution-focused brief coaching intervention delivered in conjunction with income tax preparation services at a Volunteer Income Tax Assistance location (n = 212). Individuals receiving tax preparation assistance were randomly assigned to one of four treatment groups: 1) control group; 2) video-based solution-focused brief coaching; 3) discount card incentive; 4) both the video-based solution-focused brief coaching and the discount card incentive. Results of the study indicate that the video-based solution-focused brief coaching intervention increased both the frequency and amount of self-reported savings at tax time. Results also indicate that financial therapy based interventions may be scalable through the use of technology.
Keywords: coaching; solution-focused brief coaching; VITA; savings intervention; savings motivation